2021
DOI: 10.52006/main.v4i1.316
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Happiness: A Social Study on Determinants of Well-Being among Employees in a State University

Abstract: This study aimed to elucidate the level of happiness and its influencing determinants among employees (teaching and non-teaching) of Visayas State University, Baybay City, Leyte, Philippines. With the aid of purposive sampling, the study engaged 162 employees as participants in the survey to gather richer information. The study utilized primary data, which were collected through a developed and structured questionnaires. The data were analyzed through descriptive analysis and econometric modeling. Results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…This implies that teachers are happy working and doing their responsibility as professionals during the pandemic without even thinking of a higher monetary exchange for their efforts. This finding is parallel to the result of the study of Bilal andKinza (2020), andCasinillo et al (2021), that happiness in teaching is not governed by their income but teachers are just really satisfied with their job which they found rewarding. Likewise, Benevene et al (2019) portrayed that teachers find their happiness to their students' improved performance, newly developed skills, and academic Note.…”
Section: Figuresupporting
confidence: 75%
See 2 more Smart Citations
“…This implies that teachers are happy working and doing their responsibility as professionals during the pandemic without even thinking of a higher monetary exchange for their efforts. This finding is parallel to the result of the study of Bilal andKinza (2020), andCasinillo et al (2021), that happiness in teaching is not governed by their income but teachers are just really satisfied with their job which they found rewarding. Likewise, Benevene et al (2019) portrayed that teachers find their happiness to their students' improved performance, newly developed skills, and academic Note.…”
Section: Figuresupporting
confidence: 75%
“…Secondary data was utilized in this study from a current paper by Casinillo et al (2021). The study dealt the subjective happiness and captured the influencing determinants affecting them using econometric modeling.…”
Section: Respondents and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results do not support the results of Sacks et al (2012) or Killingsworth (2021) , where a greater income was associated with greater happiness, and there were no satiation or turning points (see also Stevenson and Wolfers, 2012 ). These results are more aligned with Kahneman and Deaton (2010) , who found a satiation point in the relationship between income daily experiences of happiness, researchers finding no association between income and happiness ( Kushlev et al, 2015 ; Jebb et al, 2018 ; Casinillo et al, 2020 , 2021 ), who found that higher income can be associated with worse evaluations of life. We suggest the analytic strategy for income could contribute to explaining discrepant results in existing literature, and researchers should be clear about the approaches they have tested, although we acknowledge that sampling differences could play a role, too.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, this finding has been qualified by studies showing that the relationship between income and happiness depends on how happiness is conceptualized and measured: as an overall evaluation of one’s life or as daily emotional states ( Kahneman and Deaton, 2010 ; Killingsworth, 2021 ). In this vein, authors Kushlev et al (2015) found no relationship between income and daily happiness in the American Time Use Survey (ATUS), which has recently been found for other happiness measures, too ( Casinillo et al, 2020 , 2021 ) The finding from Kushlev et al (2015) was replicated in the German Socioeconomic Panel Survey (GSEOP) by Hudson et al (2016) , and in another analysis of the ATUS by Stone et al (2018) .…”
Section: Introductionmentioning
confidence: 92%